Effect of the Glucagon‐like Peptide‐1 Analogue Exenatide Extended Release in Cats with Newly Diagnosed Diabetes Mellitus. (24th December 2015) - Riederer, A.; Zini, E.; Salesov, E.; Fracassi, F.; Padrutt, I.; Macha, K.; Stöckle, T.M.; Lutz, T.A.; Reusch, C.E.
Abstract : Background: Exenatide extended release (ER) is a glucagon‐like peptide‐1 analogue that increases insulin secretion, inhibits glucagon secretion and induces satiation in humans with type 2 diabetes mellitus. The use of exenatide ER is safe and stimulates insulin secretion in healthy cats. Objectives: The objective of this study is to assess the safety of exenatide ER and its effect on body weight, remission and metabolic control in newly diagnosed diabetic cats receiving insulin and a low‐carbohydrate diet. Animals: Thirty client‐owned cats. Methods: Prospective placebo‐controlled clinical trial. Cats were treated with exenatide ER or 0.9% saline, administered SC, once weekly. Both groups received insulin glargine and a low‐carbohydrate diet. Exenatide ER was administered for 16 weeks, or in cats that achieved remission it was given for 4 weeks after discontinuing insulin treatment. Nonparametric tests were used for statistical analysis. Results: Cats in the exenatide ER and placebo groups had transient adverse signs including decreased appetite (60% vs. 20%, respectively, P = .06) and vomiting (53% vs. 40%, respectively, P = .715). Body weight increased significantly in the placebo group ( P = .002), but not in cats receiving exenatide ER. Cats on exenatide ER achieved remission or good metabolic control in 40% or 89%, respectively, whereas in control cats percentages were 20% or 58% ( P = .427 and P = .178, respectively). Conclusion and clinical importance: Exenatide ER is safe in diabetic cats and does not result in weight gain. Our pilot study suggests that, should there be an additional clinically relevant beneficial effect of exenatide ER in insulin‐treated cats on rate of remission and good metabolic control, it would likely approximate 20% and 30%, respectively.